Fulminant Hepatic Failure in the Course of an Outpatient Anesthetic Procedure: Sevoflurane among Other High-Risk Factors - Céline Cheron; Perrine Hoet; Nathalie Renard; Geoffroy Vanderweerden; Cristina Miscu; Mina Komuta; Pierre-François Laterre; Philippe Hantson (Case Reports in Anesthesiology)
A 20-year-old man underwent an outpatient general anesthetic procedure with sevoflurane for the correction of a bilateral gynecomastia. The patient had been first exposed to sevoflurane two years before, without any complication. He presented an overweight with a body mass index (BMI) of 31.4 kg/m2 and had an episode of “binge” drinking a few days before anesthesia. He became icteric from postoperative day 9, and after the worsening of liver function tests, the liver biopsy revealed centrilobular necrosis. The patient became encephalopathic and required urgent liver transplantation on postoperative day 30. The possibility of a sevoflurane-related fulminant hepatic failure is discussed.